2021
DOI: 10.3390/healthcare9101356
|View full text |Cite
|
Sign up to set email alerts
|

Stress Levels and Mental Well-Being among Slovak Students during e-Learning in the COVID-19 Pandemic

Abstract: The SARS-CoV-2 virus pandemic has forced far-reaching changes in higher education. Isolation from peers and distance learning have significantly limited interpersonal contacts, which might have affected the mental well-being of students. Therefore, the aim of the study was to investigate the prevalence of depressive symptoms and the level of perceived stress during e-learning among Slovak students and to identify the variables that have the most significant impact on mental health among students. The study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 47 publications
(51 reference statements)
1
31
0
Order By: Relevance
“…The mean PSS score was 19.82 in Czech Republic and 19.28 in Slovak Republic. The perception of stress by Slovak students in this study was in line with the study by Rutkowska et al ( 61 ). A slightly higher mean score was reported by French students (21.9) ( 97 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean PSS score was 19.82 in Czech Republic and 19.28 in Slovak Republic. The perception of stress by Slovak students in this study was in line with the study by Rutkowska et al ( 61 ). A slightly higher mean score was reported by French students (21.9) ( 97 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been shown in the Czech general population ( 58 , 59 ). In addition to depression and anxiety ( 60 ), Slovak students also showed increased levels of stress during the pandemic ( 61 ). There is less evidence in Czech Republic, but even in that country, it was possible to speak of worrying levels of stress, depression, and anxiety during the pandemic, not only among students but also in the general population ( 48 , 62 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors' analysis in reviews of literature, the prevalence of stress and depression in the general population as a result of the pandemic is 29 % and 33 % respectively ( 12 ) and 36% of stress and 28% of depression ( 13 ). It has also been observed that about 30% of students have symptoms of depression and 50% increased levels of perceived stress, during the COVID-19 pandemic ( 14 , 15 ). The studies presented show that students are in a group exposed to higher levels of perceived stress.…”
Section: Introductionmentioning
confidence: 99%
“…In our study in a group of medical students, the level of stress on the PSS-10 scale was 21.10 ± 5.89 points and was slightly lower than that presented in Rogowska’s research conducted in a similar period and in the study group of students with 23.53 ± 4.76 points [ 28 ]. Rutkowska’s research conducted at the same time showed a stress level of 20.85 ± 5.63 [ 29 ]. We conducted our study to assess the perceived stress in two groups of students of one medical faculty but at different stages of life, taking into account that the first group was just starting their education and the second group was almost at its end.…”
Section: Discussionmentioning
confidence: 99%